PENINGKATAN PANGSA PASAR PERUSAHAAN MAKANAN CEPAT SAJI MELALUI CUSTOMER SATISFACTION - Englysia, Irene; Sutrisno, Nuno (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this study was to determine the effect of Food Quality, Service Quality, Physical Environment Quality, and Perceived Value on Customer Satisfaction for KFC customers in DKI Jakarta. The research method used in this research is through a survey. The data analysis was done quantitatively and used a casual research design. The sampling method used in this study is to use Non-Probability Sampling with purposive sampling technique. All sample data obtained by distributing questionnaires totaled 138 respondents and will be processed using SPSS 25 software. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that Food Quality, Service Quality, Physical Environment Quality, and Perceived Value have an influence on Customer Satisfaction. This research is expected to provide input or suggestions to fast food restaurant companies, especially Kentucky Fried Chicken (KFC) restaurants which is the object of this research, is to be able to increase its competitiveness and market share in fast food restaurants in Indonesia.